The Relationship Of Parental Attention And The Development Of A Child's Marchals - Azmi, Fatarul; Azmi, Ela Fadila; Aditya, Mhd Fiqri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Attention is the activity of the soul which is directed towards an object both inside and outside itself, attention arises from the concentration of our awareness on something. In researching this journal article, the author used a qualitative method, namely by collecting various references sourced from print media related to the discussion of this research. This research aims to find out how important parental attention is to the moral development of a child and it can be seen that parental attention is very influential on the moral development of a child. If a child receives attention and education from his own parents then there is a greater possibility that the child can grow and develop has commendable morals and personality so that he can differentiate between things that are permissible to do and which things are not permissible to do.